The Association between Vitamin D Deficiency and the Prognosis of Type 2 Diabetes Mellitus - Dobrzeniecki, Krzysztof; Hopej, Natalia; Muc, Katarzyna; Turek, Kacper; Błaszczyszyn, Katarzyna; Bolek, Monika; Dardzińska, Nicol; Grzegorczyk, Aleksandra; Pachla, Magdalena (Quality in Sport, 2024)
Introduction: Type 2 diabetes mellitus is a prevalent chronic disease with high morbidity and mortality, characterized by inadequate cellular response to insulin and insufficient insulin production by pancreatic β-cells. Epidemiological studies indicate that low serum vitamin D levels are prevalent among the general population globally, exacerbating outcomes of many diseases. Recent studies suggest that vitamin D deficiency may impact type 2 diabetes mellitus prognosis. Understanding type 2 diabetes mellitus risk factors and disease progression variables is crucial for proper patient management and public health policies. Purpose of the work: This study aims to review the relationship between vitamin D deficiency and the prognosis of type 2 diabetes mellitus. Materials and methods: A comprehensive analysis of research papers available on PubMed, Google Scholar, Web of Science, Embase and Scopus was undertaken using the search terms encompassing the following keywords: vitamin D insufficiency / vitamin D supplementation / vitamin D2 / vitamin D3 / ergocalciferol / cholecalciferol and type 2 diabetes mellitus / complications of diabetes / hyperglycemia / insulin resistance / glucose metabolism. Results: Vitamin D deficiency can impact the prognosis of type 2 diabetes mellitus, exacerbating complications associated with chronic hyperglycemia such as obesity, mental health issues, vascular complications, and diabetic neuropathy. Given its prevalence among type 2 diabetes mellitus patients, early screening and supplementation of vitamin D could offer potential benefits.